STUDI LITERATUR: PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SEKOLAH DASAR - Nurul Hasna Haifa; Nurhayati; Ayu Rahayu Nurhajati; Khairunnisa Sri Handayani; Annisa Yumna Rizq; Hafiziani Eka Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Mathematical problem solving ability is one of the essential competencies that elementary school students must possess. However, in practice, many students still experience difficulties in understanding and solving mathematical problems, especially contextual problems. The low level of this ability is influenced by the use of less innovative teaching methods and the suboptimal utilization of technology in learning. This study aims to analyze the use of digital learning media in improving elementary school students’ mathematical problem solving abilities. The method used is a literature study with a qualitative descriptive approach through the review of various journals, scientific articles, and relevant previous research findings. The research data were obtained from scientific sources traced through Google Scholar and other indexed journals, then analyzed using content analysis techniques through the stages of identification, classification, and synthesis of research findings. The results of the study indicate that various digital learning media, such as Scratch, Wordwall, GeoFun, CapCut, Genially, Smart Apps Creator (SAC), interactive games, and ethnomathematics-based media, are able to significantly improve students’ mathematical problem-solving abilities. In addition to improving learning outcomes, digital media have also been proven to increase students’ motivation, engagement, and higher-order thinking skills. Therefore, digital learning media have great potential to support mathematics learning in elementary schools when designed interactively, contextually, and in accordance with students’ characteristics.